2017
DOI: 10.22161/ijeab/2.2.38
|View full text |Cite
|
Sign up to set email alerts
|

Trees Lose Their Leaves Later in Agroforestry Systems

Abstract: Abstract-In Brazilianagroforestry systems (AFS),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…The approach of the woody component can also promote competition for water, due to the higher water demand of trees. Ivanov et al (2017) compared trees from an agroforestry system with trees from a secondary forest in Caatinga, reported that the higher density of trees results in less water availability in the soil. Thus, in the east and west positions evaluated in this study, greater wilting was observed in the grown cactus pears, mainly in N. cochenillifera when subjected to conditions of moderate water stress.…”
Section: Discussionmentioning
confidence: 99%
“…The approach of the woody component can also promote competition for water, due to the higher water demand of trees. Ivanov et al (2017) compared trees from an agroforestry system with trees from a secondary forest in Caatinga, reported that the higher density of trees results in less water availability in the soil. Thus, in the east and west positions evaluated in this study, greater wilting was observed in the grown cactus pears, mainly in N. cochenillifera when subjected to conditions of moderate water stress.…”
Section: Discussionmentioning
confidence: 99%